Label-free monitoring of ambient oxygenation and redox conditions using the photodynamics of flavin compounds and transient state (TRAST) spectroscopy - Tornmalm, Johan; Widengren, Jerker (Methods (San Diego, Calif.), 2018)
[Display omitted] •Transient state (TRAST) monitoring of the flavins FMN and FAD is demonstrated.•TRAST can precisely resolve redox, triplet state and stacking kinetics in FAD/FMN.•These transitions sensitively reflect ambient oxygenation and redox conditions.•The study gives a basis for label-free monitoring of such conditions in live cells. Transient state (TRAST) monitoring can determine population dynamics of long-lived, dark transient states of fluorescent molecules, detecting only the average fluorescence intensity from a sample, when subject to different excitation pulse trains. Like Fluorescence Correlation Spectroscopy (FCS), TRAST unites the detection sensitivity of fluorescence with the environmental sensitivity of long-lived non-fluorescent states, but does not rely on detection of stochastic fluorescence fluctuations from individual molecules. Relaxed requirements on noise suppression, detection quantum yield and time-resolution of the instrument, as well as on fluorescence brightness of the molecules studied, make TRAST broadly applicable, opening also for investigations based on less bright, auto-fluorescent molecules. In this work, we applied TRAST to study the transient state population dynamics within the auto-fluorescent coenzymes flavin adenine dinucleotide (FAD) and flavin-mononucleotide (FMN). From the experimental TRAST data, we defined state models, and determined rate parameters for triplet state and redox transitions within FMN and FAD, stacking and un-stacking rates of external redox active quenching agents and by the adenine moiety of FAD itself. TRAST experiments were found to be well capable to resolve these transitions in FMN and FAD, and to track how the transitions are influenced by ambient oxygenation and redox conditions. This work demonstrates that TRAST provides a useful tool to follow local oxygenation and redox conditions via FMN and FAD fluorescence, and forms the basis for measurements on flavo-proteins and of redox and metabolic conditions in more complex environments, such as in live cells.